Characterization and control of intumescence development and leaf expansion for Capsicum annuum production in controlled environments - Dunbar, Courtney Christine, author; Craver, Joshua, advisor; Miller, Chad, committee member; Schipanski, Meagan, committee member (Colorado State University. Libraries, 2026)
Capsicum annuum (pepper) is an emerging crop for controlled environment production that is susceptible to intumescence. Intumescence is a physiological disorder characterized by unrestricted cellular elongation causing protruding lesions, ultimately leading to epidermal rupture. While the causative factor for this disorder remains unknown, water stress is commonly implicated, and end-of-day (EOD) lighting strategies have been identified as a potential strategy for mitigating intumescence development. However, the timing of pepper leaf area expansion and intumescence development as well as appropriate lighting strategies for their control have yet to be determined. The objectives of this work were to 1) determine the timing of leaf area expansion to better inform EOD or pre-dawn (PD) lighting applications for intumescence suppression; 2) quantify the impact of low-intensity lighting applications on pepper leaf morphology; and 3) determine the role of water stress in the occurrence of intumescence development for pepper. Pepper 'Pot-a-Peño', 'Spicy Jane', and 'California Wonder' were grown in 15-cm pots in a common greenhouse environment. For Objective 1, three weeks after transplant, one uniform leaf on each plant was tagged and plants were evaluated twice a day (0700 and 1900) for one week. For Objective 2, plants were subjected to 30-minute lighting treatments at an intensity of 25 μmol·m−2·s−1 for two weeks provided at either EOD with blue (EODB; 447 nm), red (EODR; 659 nm), or far-red light (EODFR; 734 nm), or PD with blue light (PDB; 447 nm). For Objective 3, plants were either maintained at 70% container capacity (control) or allowed a single dry down event reaching 40% container capacity prior to watering event. Intumescence development was visually monitored twice a day (0900) and (1700) during the water stress event. For Objective 1, leaf area expansion was greater at nighttime (NT) (1900-0700) compared to the daytime (DT) (0700-1900) with NT accounting for 66%, 57%, and 59% of total leaf area expansion for 'California Wonder', 'Pot-a-Peño', and 'Spicy Jane', respectively. For Objective 2, responses to lighting treatments were cultivar specific. For example, after two weeks, imaged leaf area was lowest under EODB for 'Pot-a-Peño' and greatest under EODFR for 'Spicy Jane'. For Objective 3, intumescence development was observed on all cultivars subjected to water stress post returning to container capacity, with no incidence of the disorder for control plants. These results will help in the prediction of intumescence development for pepper produced in controlled environments and inform decisions regarding the timing of possible suppression methods to control this disorder.